Research on lateral-longitudinal coordinated control of unmanned dump trucks in open-pit mine - PAN Guoyu; BAO Jiusheng; HU Deping; ZOU Xueyao; YIN Yan; WANG Maosen; ZHU Chenzhong; ZHANG Lei; YANG Rui (Gong-kuang zidonghua, 2024)
Open-pit mine unmanned dump trucks face harsh transportation conditions, such as low-grade roads with numerous ramps and curves, as well as heavy and highly variable loads. Most existing vehicle motion control strategies are designed for conventional road environments, making them unsuitable for direct application to mine dump trucks. To address these issues, a lateral-longitudinal coordinated control system based on preview error and layered feedback was proposed for unmanned open-pit mine dump trucks. The lateral control was based on a linear quadratic regulator (LQR) and employed a feedforward controller to reduce steady-state errors, while a fuzzy controller was used to adaptively adjust the preview distance, thereby improving path tracking accuracy. The longitudinal control established a layered feedback longitudinal speed controller, which used model predictive control and fuzzy proportional-integral-differential (PID) feedback control. In addition, an inverse model for vehicle driving and braking was established to minimize the impact of load and road gradient changes on longitudinal speed tracking. Simulation results indicated that: ① The error between the actual speed and the desired speed was within 2%, demonstrating that the speed tracking performance of the dump truck could meet requirements under both empty downhill and fully loaded uphill conditions. ② Due to the lateral-longitudinal coordinated control’s ability to adjust vehicle speed in real time based on varying road curvature, the coordinated controller achieved higher path tracking accuracy compared to single lateral control in both operating conditions, while also enhancing vehicle maneuverability and stability. Laboratory test results showed that: ① The peak lateral error during empty downhill runs was 0.0199 m, and the peak direction error was 0.1840 rad. Both errors increased at curves, but their fluctuations were minimal, ensuring that the test vehicle effectively tracked the desired path. ② During loaded uphill runs, the peak lateral error was 0.0168 m, and the peak direction error was 0.0714 rad. The error trends were opposite to those observed in empty downhill tests, but the errors remained within acceptable limits, resulting in good path tracking performance. ③ Both peak errors were lower compared to those in empty downhill tests, which validated the effect of varying speeds on lateral control accuracy.